2015
DOI: 10.1039/c4an01703j
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary Raman spectroscopic study of urine: diagnosis of breast cancer in animal models

Abstract: Prognosis of breast cancer, the most common cancer in females worldwide, has been shown to improve with early detection. Owing to disadvantages like low sensitivity, specificity, tedious sample preparation, long output times and inter-observer variance of currently available screening/diagnostic tools, rapid and objective alternatives such as Raman spectroscopy (RS) are being extensively explored. Body fluid (serum and saliva) based RS assays have shown promising results in diagnosis of oral, lung and nasophar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The confusion matrix corresponding to the PCA-LDA of SERS spectra from urine samples is presented in Figure 5b and it corresponds to a specificity of 95%, a sensitivity of 81% and an overall accuracy of 88%. For comparison, in the study by del Mistro et al on n = 20 urine samples from prostate cancer patients, the authors reported an overall accuracy of 95% [11], while in the preliminary Raman study on urine from rats with breast cancer the sensitivity and specificity reported by the authors was 80% and 72%, respectively, using unprocessed urine and 78% and 91%, respectively, using concentrated urine [10]. Thus, the results of our study are in line with previous reports on the use of Raman and SERS spectroscopy of urine for discriminating between cancer patients and controls, which reported similar figures of merit [10,11].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The confusion matrix corresponding to the PCA-LDA of SERS spectra from urine samples is presented in Figure 5b and it corresponds to a specificity of 95%, a sensitivity of 81% and an overall accuracy of 88%. For comparison, in the study by del Mistro et al on n = 20 urine samples from prostate cancer patients, the authors reported an overall accuracy of 95% [11], while in the preliminary Raman study on urine from rats with breast cancer the sensitivity and specificity reported by the authors was 80% and 72%, respectively, using unprocessed urine and 78% and 91%, respectively, using concentrated urine [10]. Thus, the results of our study are in line with previous reports on the use of Raman and SERS spectroscopy of urine for discriminating between cancer patients and controls, which reported similar figures of merit [10,11].…”
Section: Discussionmentioning
confidence: 93%
“…For instance, preliminary results in a murine model showed that Raman spectra of urine samples displayed distinguishable features in the case of rats with breast cancer [10]. Similarly, Bonifacio et al showed on n = 20 samples that the SERS spectra of urine displayed distinguishable modifications in the case of patients with prostate cancer [11].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, most studies use centrifugation as a processing step, followed by use of the supernatant for FTIR. Our previous studies have shown the effectiveness of using completely dehydrated samples for bio-fluid based study 27 . Therefore, we used two collection and three processing methods as mentioned in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…Bhattacharjee et al employed Raman spectroscopy to diagnose breast cancer using urine in a rat model and obtained classification efficiencies of 80% and 72% by using principal component analysis and principal component-linear discriminant analysis, respectively [ 14 ]. In parallel, Elumalai et al utilized Raman spectroscopy to characterize urine of normal and oral cancer patients and found that principal component analysis-based linear discriminant analysis was able to differentiate normal patients from cancer patients with an accuracy of 93.7%, a sensitivity of 98.6%, and a specificity of 87.1% [ 15 ].…”
Section: Spontaneous Raman Scattering For Cancer Diagnosismentioning
confidence: 99%